Experimental researches in electricity - Faraday, Michael 1791-1867 (Cambridge University Press, 2013)
Originally apprenticed to a bookbinder, Michael Faraday began to attend Sir Humphrey Davy's chemistry lectures purely out of interest. Although he soon recognised that science would be his vocation, there was no defined career path to follow, & when he applied to Davy for work he was gently told to 'attend to the bookbinding'. It was only after a laboratory explosion in which Davy partially lost his sight that Faraday was taken on as his amanuensis. From this difficult beginning stemmed perhaps the most famous scientific career of the 19th century. This collection of Faraday's papers provides a comprehensive record of a key branch of his work. Volume 1, reissued here in a second edition of 1849, covers his early work in electricity & magnetism, including papers on lightning, electric fish, & notes on the elaborate & often beautiful experiments conducted to investigate whether magnetism could produce electricity.